Efektivitas Pembelajaran CTL Dan Pembelajaran PBL Ditinjau Dari Prestasi Dan Motivasi Belajar Matematika Siswa Kelas II SD - Rahmawati, Putri; Danuri, Danuri (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2025)
This study was motivated by the low achievement and motivation of students to learn. Which has the aim to find out: 1. the effectiveness of CTL and PBL learning on learning achievement; 2. the effectiveness of CTL and PBL on learning motivation; 3. the effectiveness of CTL and PBL on learning achievement and motivation. This research design is a nonequivalent control group experiment. The results showed: 1. CTL has a higher average posttest score (80) than PBL (70.8), with a Sig. (2-tailed) 0.011 < 0.05, indicating that CTL is effective in improving learning achievement; 2. CTL has a higher average score of math learning motivation, namely (42.6) compared to PBL (37.4), with Sig value. (2-tailed) 0.045 < 0.05, indicating that CTL is effective in increasing math learning motivation; 3. CTL is effective in increasing achievement and learning motivation.